PERAN PENGUSAHA PEREMPUAN DALAM MENINGKATKAN SISTEM KERJA KARYAWAN DAN KOLABORASI TIM DI TOKO GALUH SIDOARJO - Adinda Diah Fatikha Yusuf, Titis Tatasari, Wafdulloh Shofa, Riessa Putra Christianto (Social Sciences Journal, 2024)
Women entrepreneurs have an increasingly significant role in shaping innovative and sustainable work systems. In this context, women entrepreneurs are not only responsible for managing the business, but also play a key role in creating a work environment that is inclusive and supports empowerment. This study aims to analyze the role of women entrepreneurs in improving employee work systems and team collaboration at Toko Galuh, Sidoarjo. Toko Galuh is managed with a team-based approach that prioritizes collaboration, where women entrepreneurs play an important role in creating a productive and inclusive work environment. Using a qualitative approach with a case study method, this research collected data through in-depth interviews with female and male employees, as well as direct observation in the workplace to further understand the work dynamics and interactions between team members. The results show that female entrepreneurs in Toko Galuh, Sidoarjo, managed to create an innovative and inclusive work system through empathic leadership and a collaboration-based approach. Despite facing some challenges, such as gender stereotypes, women entrepreneurs are able to overcome these obstacles and create a work environment that is productive, flexible and supportive of employee well-being.Keywords: Women Entrepreneurs, Employee Work System, Team Collaboration